A high centrifugal force-enhanced Ziehl–Neelsen method for improved detection of Mycobacterium tuberculosis - Godlove T. Chaula; Lucy Namkinga; Wilber Sabiiti; Nyanda E. Ntiningya; Bariki Mtafya; Ally Mahadhy (PLoS ONE, 2026)
Ziehl–Neelsen (ZN) smear microscopy remains central to tuberculosis (TB) diagnosis and treatment monitoring; however, its sensitivity is limited by incomplete recovery of Mycobacterium tuberculosis during pre-analytical processing. This study evaluated whether modifying centrifugation force and duration improves bacillary recovery and ZN smear microscopy performance. Laboratory experiments were conducted using M. tuberculosis H37Rv suspensions and clinical sputum specimens. Following NALC–NaOH treatment, samples were centrifuged at 2,000, 3,000, and 6,000 × g for 40 min. The effect of centrifugation duration was assessed at 3,000 × g by comparing 20 and 40 min using the same M. tuberculosis H37Rv cultures and the same clinical sputum specimens at both time points, ensuring paired measurements within each sample type. Smear positivity and ZN smear grading were evaluated from replicate smears and analyzed using non-parametric statistical tests, with significance set at p < 0.05. In M. tuberculosis H37Rv suspensions, no significant differences in smear positivity or grading were observed across centrifugal forces ( p = 0.368 and p = 0.212, respectively). In clinical sputum specimens, smear positivity did not differ significantly across forces ( p = 0.716), whereas ZN smear grading increased significantly with higher centrifugal force ( p = 0.0051). At 3,000 × g, extending centrifugation time from 20 to 40 min did not significantly affect smear positivity in either sample type (both p = 1.000). In contrast, ZN smear grading increased from 1+ to 2+ in clinical specimens with extended centrifugation time ( p = 0.016), while no change was observed in M. tuberculosis H37Rv suspensions. These findings indicate that increasing centrifugal force may enhance bacillary concentration in clinical sputum, resulting in improved smear grading without a corresponding increase in detection rate. Extending centrifugation time has limited impact on smear positivity. Optimization of pre-analytical centrifugation parameters may improve ZN smear microscopy performance in clinical specimens.